Is it time for a U.S. Article V Constitutional convention? A brief discussion about American constitutional reform procedure - DeSoto, Karen (Revista de Investigações Constitucionais, 2018)
This article discusses how the United States Constitution Article V Convention can be utilized to amend the constitution. Considering the intense political climate and frequent stagnation in Congress, the Article V convention is an avenue for the fifty U.S. states to spur legislative action without the cooperation of the U.S. Congress. This paper explores whether an Article V Constitutional Convention could be utilized to start the process to identify and unify critical legislative initiatives amidst the current political climate. Part II explains the function, process, and historical usage of Article V. Part III discusses case law developments interpreting Article V. Part IV examines individual state constitutional conventions and their efficacy. Part V discuss the arguments for and against an Article V Constitutional Convention.